Proses Produksi Prototipe Mesin CNC Router 3-Axis - Zoro Zulfikar; Syafri Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Productivity of small industry in Indonesia might be one of the causes of lacking of capital for the procurement of modern machine tools such as CNC (Computer Numerical Control). The purpose of this research is to make the mechanical components of CNC machine and assemble that to produce machine with cheapest prices. Therefore, the machine selling price can be reached by small industry actors. In this research, all mechanical components was made using machining process and was assembled, which using the finished components that can already be found on the market. The machining process included milling, drilling, grinding, sawing and tapping. Engine components to be assembled including of the frame, liner guide, transmission system and drive system in order to form a perfect CNC machine. Joining system of such machine components used a permanent joining such as welding, and temporary joining using bolts. The assembly also used an exchangeable assembly method, so that faster component assembly time and in replacement of damaged components that can be replaced with similar components on the market.Keywords: Prototype, CNC, Router, Machining, Joining, Assembly